Analysis of Leading Sectors in Improving the Economy East Java Province in 2016-2020 - Sutrisno, Sutrisno (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
East Java is a province that has a major influence on national GDP, therefore it is necessary to know which economic sectors can survive and be redeveloped so that the economy of East Java can return to stability as it was before the Covid-19 pandemic occurred. This research approach is a quantative research. This research uses variables, namely the economic sector. The location to carry out this research is East Java Province. The data collection methods used are documentation and literature studies. The data analysis techniques used are Location Quotient (LQ) and Dynamic Location Quotient (DLQ). There are 5 economic sectors in East Java that are included in the base sector or leading sectors at the time before the Covid-19 pandemic (2016-2019) and during the Covid-19 pandemic (2020) based on the results of the location quotient analysis. Meanwhile, based on the results of the dynamic location quotient analysis, it is known that there are 9 economic sectors in East Java Province in the 2016-2020 period which are potential sectors to be developed.